Penerapan Arsitektur Minimalist pada Omah Pulung di Semarang - Era Fazira; Sofia Sofia (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
This study examines and provides a descriptive analysis of Omah Pulung, a residential house located in Banyumanik, Semarang City, Central Java. The focus of the research is directed at the application of a minimalist architectural style that emphasizes simplicity of form, spatial efficiency, and aesthetic aspects that are in harmony with the characteristics of the building. The principles of minimalist architecture are applied through the selection of simple but functional materials, optimal natural lighting arrangements, and air circulation systems that are suitable for Indonesia's tropical climate. The research method uses a qualitative approach with observation, documentation, and descriptive analysis techniques to explore the physical and functional characteristics of the house. The results of the study show that Omah Pulung successfully represents the principle of minimalism through simple geometric shapes, efficient use of space, and natural lighting that supports the comfort of residents. In addition, good air circulation strengthens the adaptation of the house to tropical climatic conditions so that healthy and sustainable housing is created. This research contributes to the understanding of the application of minimalist architecture in the local context, as well as a reference for the development of residential design that is environmentally friendly and according to the needs of urban communities in Indonesia.